2019
DOI: 10.1074/jbc.ra118.007331
|View full text |Cite
|
Sign up to set email alerts
|

A herpesvirus transactivator and cellular POU proteins extensively regulate DNA binding of the host Notch signaling protein RBP-Jκ to the virus genome

Abstract: Reactivation of Kaposi's sarcoma-associated herpesvirus (KSHV) from latency requires the viral transactivator Rta to contact the host protein J recombination signal-binding protein (RBP-J or CSL). RBP-J normally binds DNA sequence-specifically to determine the transcriptional targets of the Notch-signaling pathway, yet Notch alone cannot reactivate KSHV. We previously showed that Rta stimulates RBP-J DNA binding to the viral genome. On a model viral promoter, this function requires Rta to bind to multiple copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 83 publications
1
14
2
Order By: Relevance
“…The copyright holder for this preprint this version posted October 22, 2022. ; https://doi.org/10.1101/2022.10.21.513206 doi: bioRxiv preprint Based on experimental data, we have published two mechanisms that describe how Rta regulates RBP-Jk DNA binding: (1) Rta directly binds to RBP-Jk, and (2) Rta induces expression of additional cellular proteins during reactivation which in turn bind to DNA adjacent to RBP-Jk (4,7,25,26). The latter mechanism is consistent with our work and others that demonstrated that de novo gene expression downstream of Rta is required for robust reactivation (25,86).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this preprint this version posted October 22, 2022. ; https://doi.org/10.1101/2022.10.21.513206 doi: bioRxiv preprint Based on experimental data, we have published two mechanisms that describe how Rta regulates RBP-Jk DNA binding: (1) Rta directly binds to RBP-Jk, and (2) Rta induces expression of additional cellular proteins during reactivation which in turn bind to DNA adjacent to RBP-Jk (4,7,25,26). The latter mechanism is consistent with our work and others that demonstrated that de novo gene expression downstream of Rta is required for robust reactivation (25,86).…”
Section: Discussionmentioning
confidence: 99%
“…Knock-down of endogenous Notch1 was confirmed via Western ). We and others have demonstrated that RBP-Jk1 binds to many sites on KSHV DNA (4-27), and we have mapped eighty-two RBP-Jk1 binding sites to the viral genome during reactivation (55). We selected six RBP-Jk1 binding sites found within 1 kb upstream of transcription start sites for KSHV genes, ie.…”
Section: Notch1 Is Necessary For Optimal Viral Reactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the expression of IE gene ORF50 encoding the replication and transcription activator protein RTA is necessary and sufficient to induce the lytic cycle of KSHV both in latently infected cells and following de novo infection [ 138 , 139 ]. RTA can induce lytic genes by binding to their promoters and recruiting epigenetic factors such as CBP/p300, SWI/SNF, mediator, and histone demethylases that can alter the viral chromatin to favor viral gene expression ( Figure 2 ) [ 140 , 141 , 142 , 143 ]. Since RTA has an E3 ubiquitin ligase activity, it can also promote lytic gene expression by inducing the degradation of host proteins repressing KSHV gene transcription [ 144 , 145 , 146 ].…”
Section: Impact Of Host Epigenetic Machinery On the Viral Life Cyclementioning
confidence: 99%
“…KSHV will enter the lytic cycle when its RTA protein is expressed. RTA is an immediate-early viral protein that is a potent viral transcription factor, which can directly induce the expression of several cellular and viral genes [ 9 , 10 , 11 , 12 , 13 ]. RTA is necessary and sufficient for the latent-lytic switch of KSHV where all viral lytic genes are expressed in a temporal, cascade-like manner: immediate-early (IE), early (E), and late (L) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%